Aportes en el uso de antena como sensor inalámbrico de sustancias volátiles (2017)
In this document it is shown the procedure that was conducted to study the dielectric properties of a coordination polymer to determine if it is capable of detecting any traces of ammonia gas. The one-dimensional coordination polymer is constituted of metallic structures of copper. For this purpose, an experiment was designed and a test protocol was developed, in order to analyze the dielectric behavior of the coordination polymer under the presence of ammonia gas. The assembly consists of a completely sealed box with a single hole on one of its sides, in which a coaxial probe is passed through. Inside the box, both the ammonia gas (with a concentration of 37%) and the coordination polymer were placed. Before designing the experimental procedure, it was a requirement to study the working principle of the coaxial probe, so that the results that would be obtained in a correct way. The results showed...